2020
DOI: 10.35940/ijitee.b6280.019320
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Thermal Pollution Effect on End Part of Stream

Mahmoud Amaal*,
El Nadi M.H.,
Nasr N. A.H.
et al.

Abstract: The present study was conducted to evaluate the environmental impact of thermal effluent sources on the main water quality parameters at the low flow conditions. The low flow causes the flow velocity to be low which causes accumulation of any pollutant source. The study was performed by creating a 2-d model of the last reach of Rosetta branch at winter closure. Delft 3d software is used to create a hydro-dynamic model to simulate the flow pattern within a 5 km of the branch upstream Edfina regulator. Water qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A previous study was performed in this area to study thermal effect on water quality parametersincluding ammonia- [12]. The study concluded that there's a positive effect of thermal effluent on ammonia as it was lowered since ammonium solubility decreases with increasing temperature for the same PH [13], So, hypochlorite acid reacts with low concentrated ammonia -after being lowered from high temperature-and produce chloramines.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study was performed in this area to study thermal effect on water quality parametersincluding ammonia- [12]. The study concluded that there's a positive effect of thermal effluent on ammonia as it was lowered since ammonium solubility decreases with increasing temperature for the same PH [13], So, hypochlorite acid reacts with low concentrated ammonia -after being lowered from high temperature-and produce chloramines.…”
Section: Discussionmentioning
confidence: 98%